2017
DOI: 10.1002/cbdv.201700231
|View full text |Cite
|
Sign up to set email alerts
|

Constituents from Scutellaria barbata Inhibiting Nitric Oxide Production in LPS‐Stimulated Microglial Cells

Abstract: The arial parts of Scutellaria barbata D. Don (Lamiaceae) efficiently inhibited NO production in BV2 microglial cells, and the active constituents were further isolated based on activity-guided isolation using silica-gel column chromatography, RP-C18 MPLC and prep-HPLC. As the results, 2 flavonoids including 6-methoxynaringenin (1) and 6-O-methylscutellarein (5), and 6 neo-clerodane diterpenes such as scutebarbatine W (2), scutebatas B (3), scutebarbatine B (4), scutebarbatine A (6), 6-O-nicotinolylscutebarbat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Scutellaria barbata, a traditional anticancer Chinese medicine, has been found to have the additional effect of anti-inflammation and anti-infection in recent years. Diterpenoid alkaloids and 6-methoxynaringenin in the Scutellaria barbata extracts had the strongest effect on downregulating the secretion of NO, PE2, IL-6, IL-1 β induced by LPS and P-JNK signaling pathway activation [4244]. Moreover, the water extracts of Bittersweet herb and Herba artemisiae scopariae can alleviate inflammation by inhibition of NF- κ B pathway that reduces the generation of proinflammatory cytokines like IL-1 β and IL-6 [4547].…”
Section: Discussionmentioning
confidence: 99%
“…Scutellaria barbata, a traditional anticancer Chinese medicine, has been found to have the additional effect of anti-inflammation and anti-infection in recent years. Diterpenoid alkaloids and 6-methoxynaringenin in the Scutellaria barbata extracts had the strongest effect on downregulating the secretion of NO, PE2, IL-6, IL-1 β induced by LPS and P-JNK signaling pathway activation [4244]. Moreover, the water extracts of Bittersweet herb and Herba artemisiae scopariae can alleviate inflammation by inhibition of NF- κ B pathway that reduces the generation of proinflammatory cytokines like IL-1 β and IL-6 [4547].…”
Section: Discussionmentioning
confidence: 99%
“…The plates were then incubated for an additional 24 h at 37 °C. The NO production was determined using Griess reagents [49]. The supernatant was mixed with an equal volume of the sulfanilamide solution and incubated at 37 °C for 10 min in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…Scutellaria barbata has a potent antitumor activity in breast cancer [17], colorectal cancer [18], hepatocarcinoma [19], skin cancer [20], lung cancer [21], and ovarian cancer [22]. Moreover, Lee et al, (2017) [23] reported that the active fractions of Scutellaria barbata have antiinflammatory activity in BV-2 cells. The present research study was mainly focused on the synthesis of gold nanoparticles from the Scutellaria barbata by green route method and evaluation of its anticancer activity against pancreatic cancer cell lines (PANC-1).…”
Section: Introductionmentioning
confidence: 99%